2017
DOI: 10.1002/jcsm.12188
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive proteome analysis of human skeletal muscle in cachexia and sarcopenia: a pilot study

Abstract: BackgroundCancer cachexia (cancer‐induced muscle wasting) is found in a subgroup of cancer patients leaving the patients with a poor prognosis for survival due to a lower tolerance of the chemotherapeutic drug. The cause of the muscle wasting in these patients is not fully understood, and no predictive biomarker exists to identify these patients early on. Skeletal muscle loss is an inevitable consequence of advancing age. As cancer frequently occurs in old age, identifying and differentiating the molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 45 publications
4
40
1
Order By: Relevance
“…This is also true for sarcopenia in healthy ageing. 31,32 It has been established that patients with HF and sarcopenia have impaired endothelium function with lower vasodilation having a negative impact of exercise capacity, which is particularly prevalent in sarcopenic patients. On the other hand, decreased exercise capacity and decreased physical activity act hand in hand in aggravating skeletal muscle loss, in itself accelerated by an imbalance in protein senescence and degradation.…”
Section: Screening and Diagnosing Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…This is also true for sarcopenia in healthy ageing. 31,32 It has been established that patients with HF and sarcopenia have impaired endothelium function with lower vasodilation having a negative impact of exercise capacity, which is particularly prevalent in sarcopenic patients. On the other hand, decreased exercise capacity and decreased physical activity act hand in hand in aggravating skeletal muscle loss, in itself accelerated by an imbalance in protein senescence and degradation.…”
Section: Screening and Diagnosing Sarcopeniamentioning
confidence: 99%
“…30 The human skeletal muscle proteome project is currently underway to characterize muscle proteins and the way they change during ageing and disease. 31,32 It has been established that patients with HF and sarcopenia have impaired endothelium function with lower vasodilation having a negative impact of exercise capacity, which is particularly prevalent in sarcopenic patients. 33 Anorexia is likewise very prevalent in patients with HF as assessed using a 6-point Likert scale.…”
Section: Screening and Diagnosing Sarcopeniamentioning
confidence: 99%
“…It did not come as a surprise that they won the poster price for this presentation. Alexander Ebhardt et al . (Systems Biology Ireland) gave an overview of ageing effects in myogenesis.…”
Section: Basic Sciencementioning
confidence: 99%
“…It did not come as a surprise that they won the poster price for this presentation. Alexander Ebhardt et al 10 (Systems Biology Ireland) gave an overview of ageing effects in myogenesis. He showed that highly regulated proteins in foetal are dysregulated in ageing 83 years as function of myogenesis.…”
Section: Basic Sciencementioning
confidence: 99%
“…However, these studies were limited in size, focused on cancer cachexia, analyzed single fibers, did not account for levels of physical activity or did not explore the effect of aging over its continuous range and, therefore, could not distinguish changes due to aging from those due to disease or sedentary state [14][15][16][17][18] . To overcome these earlier limitations, we have performed a quantitative mass spectrometry-based proteome analysis (tandem mass tag, TMT) of skeletal muscle biopsies obtained from individuals distributed over a wide age range, who were extremely healthy based on strict objective clinical criteria.…”
Section: Introductionmentioning
confidence: 99%